Technisches Lernen inklusiv gestalten – Zur Beschaffenheit von Lernbedürfnissen im Kontext technikbezogenen Sachunterrichts - Schröer, Franz (Technikunterricht: handfest und geistreich - Der Beitrag technischer Bildung zur kulturellen Bildung - Tagungsband zur 21. Tagung der Deutschen Gesellschaft für Technische Bildung in Flensburg vom 20.-21. September 2019. Offenbach am Main)
Der Gedanke einer inklusiven Schule als einer Schule für alle Kinder ist, wenn auch aus der Perspektive von 100 Jahren Grundschule erst kürzlich durch die UN-Konvention über die Rechte von Menschen mit Behinderung (United Nations 2006) verstärkt, als an das Bildungssystem gerichtete Anforderung unbestritten. Die Didaktik des Sachunterrichts als wissenschaftliche Disziplin und als Instanz technikbezogenen Lernens in der Grundschule hat sich dem Thema Inklusion mit den Untersuchungen von Seitz (2005) und Schomaker (2000), für eine fachdidaktische Disziplin vergleichsweise früh zugewendet (Pech & Schomaker 2013, S. 341). Pech, Schomaker & Simon (2018, S. 12ff.) arbeiten jedoch an begrifflichen Unschärfen in einschlägigen Veröffentlichungen heraus, dass es in der Sachunterrichtsdidaktik bis heute keinen systematischen Diskurs darüber gibt, wie Inklusion zu verstehen, zu entwickeln und zu implementieren ist. Die allgemeinpädagogisch unter anderem von Feuser (2011, S. 89) für das Bildungssystem formulierte Entwicklungsaufgabe von der Segregation über die Integration zur Inklusion findet sich in Abhängigkeit von der Perspektive unterschiedlich definiert in der Sachunterrichts- bzw. Fachdidaktik wieder. Da bei der Definition von inklusivem Sachunterricht unterschiedliche wissenschaftliche Kontexte (z.B. sonderpädagogische, inklusionspädagogische oder allgemeindidaktische) zur Argumentation herangezogen werden, ist im Folgenden häufiger von der Rekontextualisierung von Inklusion in der Fachdidaktik die Rede. Die Berücksichtigung von Lernbedürfnissen und die Nutzung von individuellen Potenzialen stellt eine sich in der Sachunterrichtsdidaktik (u.a. Lichtblau 2014, S. 204; Simon 2014, S. 241; Pech, Schomaker & Simon 2018, 15f.) wie in der allgemeinen Pädagogik (Feuser 1989, S. 9; Schumann 2009, S. 51; Preuß 2018, S. 81) wiederholende Rekontextualisierung zur Beschreibung inklusiven Unterrichts dar. Potenzialorientierte (fach-)didaktische Überlegungen, also solche, die eine Orientierung an in Personen liegenden Defiziten auf der einen und standardisierten Normen auf der anderen Seite ablehnen und den Blick vermehrt auf die im Individuum, dem Fach oder einem Lerngegenstand liegenden Potenziale für eine gleichberechtigte und gleichwertige Partizipation aller Lernenden richten (Simon 2019, S. 114), erfahren derzeit vermehrt Aufmerksamkeit. Die Berücksichtigung individueller Lernbedürfnisse auf der anderen Seite bleibt in einschlägigen Veröffentlichungen dagegen oftmals theoretisch unreflektiert. Ausgehend davon leistet das vorgestellte Dissertationsvorhaben mit Blick auf technikbezogenes Lernen im Sachunterricht der Grundschule einen theoriebildend angelegten Beitrag zur Verbindung von erziehungswissenschaftlicher und sachunterrichtsdidaktischer Inklusionsforschung am Lerngegenstand Technik. Die Studie ist, ob der Offenheit des Forschungsfeldes bezogen auf technikbezogenen Sachunterricht im Kontext von Inklusion, überwiegend qualitativ-rekonstruktiv angelegt. Unter der Rekontextualisierung von Inklusion als Berücksichtigung zunehmend vielfältiger Lernbedürfnisse im Sachunterricht, fragt die Studie nach der Beschaffenheit und Dimensionen der Verschiedenheit von Lernbedürfnissen sowie Möglichkeiten bzw. Hindernissen auf dem Weg zu ihrer Berücksichtigung.
Keywords: Inclusion; Sachunterricht; basic needs; technology education

Ethical Considerations of Applying Robots in Kindergarten Settings: Towards an Approach from a Macroperspective - Tolksdorf, Nils F.; Siebert, Scarlet; Zorn, Isabel; Horwath, Ilona; Rohlfing, Katharina J. (International Journal of Social Robotics)
In child–robot interaction (cHRI) research, many studies pursue the goal to develop interactive systems that can be applied in everyday settings. For early education, increasingly, the setting of a kindergarten is targeted. However, when cHRI and research are brought into a kindergarten, a range of ethical and related procedural aspects have to be considered and dealt with.While ethical models elaborated within other human–robot interaction settings, e.g., assisted living contexts, can provide some important indicators for relevant issues, we argue that it is important to start developing a systematic approach to identify and tackle those ethical issues which rise with cHRI in kindergarten settings on a more global level and address the impact of the technology from a macroperspective beyond the effects on the individual. Based on our experience in conducting studies with children in general and pedagogical considerations on the role of the institution of kindergarten in specific, in this paper,we enfold some relevant aspects that have barely been addressed in an explicit way in current cHRI research. Four areas are analyzed and key ethical issues are identified in each area: (1) the institutional setting of a kindergarten, (2) children as a vulnerable group, (3) the caregivers’ role, and (4) pedagogical concepts. With our considerations, we aim at (i) broadening the methodology of the current studies within the area of cHRI, (ii) revalidate it based on our comprehensive empirical experience with research in kindergarten settings, both laboratory and real-world contexts, and (iii) provide a framework for the development of a more systematic approach to address the ethical issues in cHRI research within kindergarten settings.
Keywords: Robot ethics · Kindergarten settings · Child–robot interaction · Early childhood education

Professional knowledge affects action-related skills: The development of preservice physics teachers’ explaining skills during a field experience - Kulgemeyer, Christoph; Borowski, Andreas; Buschhüter, David; Enkrott, Patrick; Kempin, Maren; Reinhold, Peter; Riese, Josef; Schecker, Horst; Schröder, Jan; Vogelsang, Christoph (Journal of Research in Science Teaching)
Keywords: Education

Situative Beobachtung und Wahrnehmung angehender frühpädagogischer Fachpersonen im Bereich Mathematik – Entwicklung und Validierung eines Testinstruments - Bruns, Julia; Strahl, Carolin; Gasteiger, Hedwig (Unterrichtswissenschaft)
Zusammenfassung Frühe mathematische Bildung findet in der Kindertagesstätte insbesondere in spontanen Alltagssituationen statt. Damit diese Alltagssituationen zu natürlichen Lernsituationen für die Kinder werden, müssen (angehende) frühpädagogische Fachkräfte zunächst das mathematische Potenzial in diesen Situationen erkennen. Diese Fähigkeit zur situativen Beobachtung und Wahrnehmung ist bisher unzureichend erforscht, was unter anderem auf begrenzte Methoden zur standardisierten Erfassung dieses Konstrukts zurückzuführen ist. Um diesem Bedarf zu begegnen, wurde das videobasierte Testinstrument Vimas_num zur Erfassung der Fähigkeit zur situativen Beobachtung und Wahrnehmung angehender frühpädagogischer Fachpersonen im Bereich Mengen und Zahlen entwickelt. Auf der Grundlage von drei aufeinander aufbauenden Studien wird die Validität verschiedener Aspekte der Testwertinterpretation untersucht. Die Ergebnisse geben Hinweise auf die Validität der Testwertinterpretation in Bezug auf den Testinhalt, die interne Struktur des Tests und die Zusammenhänge mit theoretisch verbundenen Konstrukten.
Keywords: Education

Christian Efing / Karl-Hubert Kiefer (Hg.): Sprachbezogene Curricula und Aufgaben in der beruflichen Bildung. Aktuelle Konzepte und Forschungsergebnisse - Prikoszovits, Matthias (Deutsch als Fremdsprache)
Keywords: Computer Science Applications; History; Education

Motivation of out-of-field teachers for participating in professional development courses in mathematics - Lünne, Steffen; Schnell, Susanne; Biehler, Rolf (European Journal of Teacher Education)
Keywords: Education

Students’ Understanding of the Derivative Concept in the Context of Mathematics for Economics - Feudel, Frank; Biehler, Rolf (Journal für Mathematik-Didaktik)
Abstract The derivative concept plays a major role in economics. However, its use in economics is very heterogeneous, sometimes inconsistent, and contradicts students’ prior knowledge from school. This applies in particular to the common economic interpretation of the derivative as the amount of change while increasing the production by one unit. Hence, in calculus courses for economics students, learners should acquire an understanding of the derivative that is mathematically acceptable and connected to their prior knowledge, but which also takes into account its practical use in economics. In this paper we first develop a theoretical model describing such an understanding of the derivative for economics students. We then present an exploratory study investigating the extent to which economics students have such an understanding after their calculus course. The results indicate that many of them might not have acquired this kind of understanding, in particular concerning the common economic interpretation of the derivative. The study furthermore yields possible gaps in students’ understanding and possible misconceptions.
Keywords: Education; General Mathematics

Mathematics learning support centres in Germany—an overview - Schürmann, Mirko; Gildehaus, Lara; Liebendörfer, Michael; Schaper, Niclas; Biehler, Rolf; Hochmuth, Reinhard; Kuklinski, Christiane; Lankeit, Elisa (Teaching Mathematics and its Applications: An International Journal of the IMA)
Abstract Mathematics learning support centres (MLSC) are widely established and evaluated in English-speaking countries (such as the UK, Ireland and Australia). In most of these countries, several national surveys on MLSCs exist. They give an overview of the number of MLSCs as well as their characteristics in these countries. In Germany, there is a lack of studies on MLSCs and the landscape of MLSCs has not been described yet. This article presents basic information concerning counts of MLSCs and their characteristics at universities. Based on a three-step approach of analysing university homepages and additional personal contact via email or phone calls, we gathered typical MLSC features (e.g. staff quantities and qualification, opening and support hours, supported study programmes). We analysed 190 universities from a web-based register on study programmes. In total, we found 61 MLSCs located at 51 German universities. Another 16 support centres were specialized on mathematics didactics, which means they focussed on didactical and methodological support for preservice teacher students and often provided different teaching materials. Thirty-eight centres were located at universities (62.3%) and 23 MLSCs at universities of applied sciences and comparable universities (37.7%). The MLSCs were different in their sizes of staff and opening hours, and both the numbers of staff and the service hours differed greatly. The student groups MLSCs at German universities focus on differ concerning characteristics like study programme or semester. We will provide the main categories describing these groups. We seek to answer research questions concerning the characteristics of MLSCs in Germany and discuss the results compared to international findings. This information is useful for further international collaborative research, for example a standardized international survey. From a national perspective, these findings support networking and collaborations between the MLSCs as well. As some German MLSCs are facing financial cuts, these results might help in gaining additional funding.
Keywords: Education; General Mathematics

Liberating or indoctrinating? Surveying students’ perceptions of a Womens’ and Gender Studies requirement - Horwath, Ilona; Diabl, Christian (Gender and Education)
This article offers new insight into students’ responses to Womens’ and Gender Studies (WGS) classes by overcoming the self-selection bias hitherto inherent in the field. Exploring the experiences of 1406 students (770 women, 636 men) of a university with a WGS requirement across all study programmes, we examine the prevailing discourses on WGS, participants’ (dis)agreement as well as personal and professional benefits gained through WGS. Additionally, we evaluate the perceived value of WGS for themselves, in society, and of WGS opportunities in higher education. Findings reveal a gender bias regarding discourses, experience, benefit, and value, with 70.1% women and 32.4% men supporting the idea of WGS as a mandatory subject. Women’s support indicates a need for tools to negotiate gender issues, while men’s resistance serves to defend male privileges. We conclude that a requirement of WGS classes amplifies the potential for both – resistance and change.
Keywords: Education policy; equality; higher education; critical pedagogies; gender mainstreaming; curriculum

Assessing dimensions of inclusion from students’ perspective – measurement invariance across students with learning disabilities in different educational settings - Knickenberg, Margarita; Zurbriggen, Carmen; Venetz, Martin; Schwab, Susanne; Gebhardt, Markus (European Journal of Special Needs Education)
Keywords: Developmental and Educational Psychology; Health Professions (miscellaneous); Education

European educational research (re)constructed: institutional change in Germany, the United Kingdom, Norway, and the European Union - Pöllmann, Andreas (Compare: A Journal of Comparative and International Education)
Keywords: Education

Gamification in an Augmented Reality Based Virtual Preparation Laboratory Training - Alptekin, Mesut; Temmen, Katrin (The Challenges of the Digital Transformation in Education)
Through technological progress during recent years, Augmented Reality (AR) technology can be used on ordinary smartphones with applications (Apps) in many formal and informal learning environments and educational institutions (e.g. [1, 2]). It is emerging as a suitable technology for teaching psychomotor skills. Simultaneously, gamification has become increasingly popular in the teaching field, providing famous examples, such as Duolingo (for the acquisition of foreign languages) or Codecademy (for learning programming languages) [3]. Many papers have already highlighted the beneficial aspects of gamification and AR for education and teaching (e.g. [1, 2, 4, 5]. While gamification is useful for improving students’ motivation and engagement, AR can be applied to teach them operational skills without any time, costs and place constraints. Hence, this opens up numerous possibilities and forms to combine these two aspects (AR and gamification) for higher education teaching. However, there has been less research focusing on how gamification and AR can be combined in a useful manner to keep up students’ initial motivation aroused through novelty effects of AR learning environments. Accordingly, this paper will present such a gamification concept for an AR based virtual preparation laboratory training to overcome the risk of demotivation, once AR will settle as a mainstream technology such as learning videos. The focus of the AR-App – presently being developed at the University of Paderborn – is to remedy the students’ lack of practical skills when operating electro-technical laboratory equipment during their compulsory laboratory training.
Keywords: Augmented Reality; Laboratory Training; Engineering Education; Gamification

Teaching an Oscilloscope through Progressive Onboarding in an Augmented Reality Based Virtual Laboratory - Alptekin, Mesut; Temmen, Katrin (2019 IEEE Global Engineering Education Conference (EDUCON))
The first impression is important in many aspects of human decision-making. In mobile apps, this impression can be influenced by an onboarding process. In addition, not only the user experience (UX) can be improved via onboarding, but also the user can get a very good didactical introduction to a new topic or different functionalities of an app. Therefore, this study examines different onboarding types and develops an onboarding process into an Augmented Reality (AR) based mobile application (app) that teaches students how to use and operate electro-technical laboratory equipment. This onboarding process is then assessed by students through a subsequent questionnaire in terms of attractiveness, functionality, and novelty. The results of this field study serve to examine this first prototype for possible optimizations and to further develop the app accordingly.
Keywords: Augmented Reality; Laboratory Training; Engineering Education; Progressive Onboarding

Vocabulary in learning processes towards conceptual understanding of equivalent fractions—specifying students’ language demands on the basis of lexical trace analyses - Wessel, Lena (Mathematics Education Research Journal)
Abstract Although the teaching of vocabulary in mathematics lessons is requested in content- and language-integrated lesson designs, the clarification of the specific lexical language demands is still an open question for many mathematical topics. In a content- and language-integrated lesson design towards understanding the concept of equivalent fractions, the vocabulary (words and phrases) used by 17 students has been analyzed with qualitative means of data analysis. The qualitative in-depth analyses underline the importance of meaning-related vocabulary for making structural relations between the fractions in view explicit. Quantitative analyses of inventoried vocabulary for the four categories “self-initiated by students,” “triggered by teaching material,” “triggered by teacher,” or “triggered by peers” show the relations of collective and autonomous vocabularies from which the students retrieve their lexical means in oral and written language production.
Keywords: Education; General Mathematics

How theories of language-responsive mathematics can inform teaching designs for vocational mathematics - Wessel, Lena (Eleventh Congress of the European Society for Research in Mathematics Education (CERME11))
Keywords: Vocational education; language; percentages; scaffolding; design research

Language diversity and mathematics education: new developments - Barwell, Richard; Wessel, Lena; Parra, Aldo (Research in Mathematics Education)
Keywords: General Mathematics; Education

FROM EMPOWERMENT TO INNOVATION: INTER- AND TRANSDISCIPLINARY RESEARCH METHODS IN LIGHTWEIGHT ENGINEERING - Horwath, Ilona; Dohmeier-Fischer, Silvia; Weiß-Borkowski, Nathalie; Tröster, Thomas (INTED2018 Proceedings)
Inter- and transdisciplinary research are new demands in Higher Education. Aiming to enhance the social relevance, usability and sustainability of technological products and solutions, society and public institutions such as research funding organizations increasingly expect engineers to include inter- and transdisciplinary approaches into the development of new technologies. Engineering research and education, however, are particularly challenging areas to realize inter- and transdisciplinary collaborations, for manifold reasons. This contribution presents methods and results of an inter- and transdisciplinary research and education strategy designed to meet the particular requirements of engineers and engineering students. It starts with a brief discussion of typical challenges regarding inter- and transdisciplinary approaches in engineering (research topics, research culture, skills, time, and barriers of lay people to involve in technology development). Secondly, it presents the methods developed to overcome those challenges within the context of the NRW Fortschrittskolleg "Light - Efficient - Mobile" (FK LEM). Founded in 2014, the FK LEM is a PhD programm focuses on lightweight construction, but with a special emphasis on how lightweight technologies are connected to different areas of society, to societal actors and technology users, and to the needs of a diversity of social groups. In order to explore these connections, we organized three workshops to bring public service, civil society, industry, practitioners and engineers together to discuss the perceived needs in those areas, and the potential of lightweight solutions. Topically, the workshops were dedicated to the fields of Rescue & Security Services; Care, Mobility & Assisted Living; and Sustainable Ressources & Climate Protection. Methodologically, we applied a pragmatic but valid approach to focus groups and discourse analysis. Results of the workshops in terms of directions for future research, epistemological and ethical dimensions of lightweight engineering are presented in the third part of our contribution. Finally, we discuss how our method and experience can be transferred into other engineering and educational contexts. With other words, how empowering students, engineers and the public to involve in inter- and transdisciplinary engineering processes can be achieved, and how this empowerment supports the development of innovative technologies as well as engineers’ skills to design technology in line with societies’ needs and challenges.
Keywords: Lightweight Design; Interdisciplinarity; Transdisciplinarity; Higher Education; Research Methods

Reciprocal effects between self-concept of ability and performance: A longitudinal study of children with learning disabilities in inclusive versus exclusive elementary education - Gorges, Julia; Neumann, Phillip; Wild, Elke; Stranghöner, Daniela; Lütje-Klose, Birgit (Learning and Individual Differences)
Ample empirical research from regular school settings documents reciprocal effects between academic performance and academic self-concept of ability (ASC), supporting what is known as a reciprocal effects model (REM). The present article investigates a REM in the domain of reading performance in a sample of elementary students with special educational needs in learning (SEN-L) who received special educational support in exclusive versus inclusive settings (N = 446). In exclusive settings, SEN-L students attend special schools and are completely separated from regular students. By contrast, SEN-L students in inclusive settings attend regular schools and are educated in classes with regular students. In both settings, SEN-L students are not graded and taught based on individual learning goals, which may affect reciprocal effects between ASC and reading performance. In addition, given that special education for SEN-L students relies heavily on individual reference standards to evaluate performance, we tested individual performance growth of SEN-L students as a predictor of ASC. Analyses of a longitudinal dataset across 3rd and 4th grade revealed some cross-lagged effects and an effect of performance growth on ASC in exclusive settings in particular. The discussion focuses on the role of individualized instruction, grades, peer groups, and individual versus social reference standards for reciprocal effects between ASC and performance as well as practical implications.
Keywords: BiLieF; Special educational needs; Learning disability; Academic selfconcept of ability; Reciprocal effects model; Inclusive education

La formación intercultural de los futuros maestros mexicanos de secundaria - Pöllmann, Andreas (Revista Electrónica de Investigación Educativa)
La provisión de oportunidades para el aprendizaje intercultural a través del contacto con “lo extranjero” es fundamental para el bienestar cultural, social y económico de los países multiculturales. El contexto mexicano es de particular interés tanto por su extraordinaria diversidad sociocultural como por sus niveles epidémicos de analfabetismo intercultural. Con base en una encuesta realizada a 189 estudiantes de la Escuela Normal Superior de México, el presente artículo explora (i) la importancia percibida del contacto con “lo extranjero” como parte de la formación magisterial, (ii) el interés existente por la participación en algún programa de intercambio internacional y (iii) el nivel de experiencias concretas con “lo extranjero”. A partir de una serie de estadísticas descriptivas –que demuestran las percepciones, intereses y experiencias de los futuros maestros de secundaria– se manifiesta la importancia de un mayor compromiso institucional y gubernamental con la formación intercultural del magisterio normalista.
Keywords: Education

Evaluating Innovative Measures in University Mathematics – The Case of Affective Outcomes in a Lecture focused on Problem-Solving - Kuklinski, Christiane; Leis, Elena; Liebendörfer, Michael; Hochmuth, Reinhard; Biehler, Rolf; Lankeit, Elisa; Neuhaus, Silke; Schaper, Niclas; Schürmann, Mirko (Proceedings of the Second Conference of the International Network for Didactic Research in University Mathematics (INDRUM 2018, 5-7 April 2018))
The transition from high school to university mathematics has proven to be difficult for many students but especially for pre-service secondary teachers. To support these students at mastering this transition, various universities have introduced support measures of various kinds. The WiGeMath project developed a taxonomy that makes it possible to describe and compare these measures concerning their goals as well as their frame characteristics. We will exemplify the use of the taxonomy in the description of one specific innovative measure that was part of the WiGeMath evaluations. Moreover, we will present first results concerning the goal-fulfilment of this measure concerning affective characteristics of the student cohort and their predominant beliefs.
Keywords: Beliefs.; Motivational developments; Novel approaches to teaching; Teacher education; Transition to and across university mathematics

From professional knowledge to professional performance: The impact of CK and PCK on teaching quality in explaining situations - Kulgemeyer, Christoph; Riese, Josef (Journal of Research in Science Teaching)
Keywords: Education

Theoretical frameworks for designing and analyzing language-responsive mathematics teaching–learning arrangements - Wessel, Lena; Erath, Kirstin (ZDM)
Keywords: General Mathematics; Education

The interplay between subjective abilities and subjective demands and its relationship with academic success. An application of the person–environment fit theory - Bohndick, Carla; Rosman, Tom; Kohlmeyer, Susanne; Buhl, Heike M. (Higher Education)
In this study, we draw on person–environment fit theory to analyze whether academic success is best explained by individual abilities subjectively exceeding situational demands or by abilities matching the demands. Moreover, we disentangled effects of perceived abilities and subjective person–environment (P-E) fit on academic success. All in all, 693 teacher education students participated in an online questionnaire. Students were asked to rate general requirements of their academic programs (e.g., self-discipline) on a 5-point scale in terms of (1) their own abilities and (2) the perceived relevance for their studies. P-E fit was determined by difference scores between abilities and relevance ratings. Academic success was assessed by grades, perceived performance, and study satisfaction. Data were analyzed through structural equation modeling and suggest that academic success is best explained by a match between abilities and demands. Moreover, all three criteria for academic success were more strongly related to subjective fit than to subjective abilities.
Keywords: Academic success; Person–environment fit theory; Demands–abilities fit; Higher education

Competencies and career choice motives: characteristics of high school students interested in teacher education programmes - Bohndick, Carla; Kohlmeyer, Susanne; Buhl, Heike M. (Journal of Education for Teaching)
In contrast to other career choices, the teaching profession seems familiar to those interested in teaching because they have had the chance to observe teachers for years. This phenomenon is known as the apprenticeship of observation and manifests in naïve ideas and expectations of teaching among teacher students. Therefore, characteristics of students interested in becoming teachers are important for early teacher education and counselling. These characteristics include competencies and motives, but nothing is known about their relationship to each other. Following international teaching standards and the expectancy-value framework, this paper analyses associations between both. Three competencies (i.e. planning, communication and cooperation) and seven career choice motives were examined using a paper–pencil survey of 907 high school students. Altogether, 463 students were able to imagine becoming a teacher and were included in the analyses. SEM analyses showed that (1) of all the competencies, communication had the most associations with motives, (2) the motive ‘low difficulty of study’ is positively related to planning, (3) the findings regarding extrinsic motives are ambiguous, and (4) gender differences are marginal. Practical implications for early teacher education and counselling are discussed.
Keywords: Education

Six-year-olds' perception of home literacy environment and its influence on children's literacy enjoyment, frequency, and early literacy skills - Wiescholek, Sabrina; Hilkenmeier, Johanna; Greiner, Christian; Buhl, Heike M. (Reading Psychology)
Home literacy environment (HLE) makes an important contribution to children's reading acquisition in early years. Even though some research on children's perception exists, children's reports about HLE have been neglected. The present study focuses on N = 281 six-year-old's reports about HLE and its influences on literacy enjoyment, frequency, and early literacy skills. Parents' educational background was expected to predict children-perceived HLE. A positive impact of active HLE on literacy enjoyment and frequency were found. HLE also mediates the relation between parents' background and enjoyment. The importance of children's perspective on HLE regarding family literacy programs is discussed.
Keywords: Linguistics and Language; Developmental and Educational Psychology; Education

The Role of Parents and Peers in the Transition From University to Work Life - Buhl, Heike M.; Noack, Peter; Kracke, Baerbel (Journal of Career Development)
This longitudinal study addresses the role of support given by parents and peers during the transition from university to work life. A sample of 64 German university students in their last year at the university completed scales from the Network of Relationships Inventory regarding general support, namely, instrumental aid and intimacy with mothers, fathers, romantic partners, and friends. Four years later, they assessed domain-specific support when looking for work, namely, joint exploration and instrumental support. Participants perceived receiving both types of support from all significant others. However, joint exploration was more important than instrumental support. They felt especially supported by romantic partners. Women received more support than did men. Both types of domain-specific support were explained by general modes of support assessed 4 years earlier. Whether parents, friends, and partners were perceived as helpful during the transition was explained mainly by joint exploration. Again, support from a partner was seen as especially helpful in contrast to help from parents and friends. The special significance of joint exploration underlines the benefit of counseling at the transition from university to work life.
Keywords: Organizational Behavior and Human Resource Management; General Psychology; Applied Psychology; Education

Das Praxissemester fachdidaktisch in den Blick nehmen - Wosnitza, Christopher; Caruso, Carina; Vogelsang, Christoph (die hochschullehre)
In vielen Bundesländern ist ein Praxissemester obligatorischer Bestandteil der Lehramtsausbildung. Zunehmend wird untersucht, ob und in welcher Form Studierende die für diesen Ausbildungsabschnitt vorgesehenen Standards erreichen. Dabei fokussieren Untersuchungen primär bildungswissenschaftliche Kompetenzbereiche. Die Frage, inwiefern das Praxissemester zum Erwerb domänenspezifischer bzw. insbesondere fachdidaktischer Kompetenzen beiträgt, lässt sich als Forschungsdesiderat konstatieren. Es ist zudem unklar, wie bestimmte Lerngelegenheiten diesen Prozess beeinflussen. Um diesem Forschungsbedarf zu begegnen, wurde an der Universität Paderborn die interdisziplinäre Forschungsgruppe Fachdidaktische Forschung im Praxissemester gegründet. Ziel der gemeinsamen Arbeit ist es, auf Basis wissenschaftlicher Ergebnisse einen Beitrag zur Weiterentwicklung des Praxissemesters zu leisten. Am Praxissemester sind drei Ausbildungsorte beteiligt: Hochschulen, Zentren für schulpraktische Lehrerausbildung (ZfsL) und Schulen. Ein Schwerpunkt liegt daher auf der Untersuchung des kritisch-produktiven Verhältnisses von Hochschullehre und Praxis. Vor dem Hintergrund fachübergreifender Heuristiken zur Professionalisierung in der Lehrer/innenbildung, werden in diesem Artikel aktuelle Projekte der Forschungsgruppe und deren Kontexte vorgestellt und diskutiert.
Keywords: Praxissemester; Lehrer/innenbildung; Evaluation; Kompetenzentwicklung; Fachdidaktik / school internships; teacher education; evaluation; professional competence; subject matter education

INFLUENCES ON TEACHERS’ JUDGMENT ACCURACY OF READING ABILITIES ON SECOND AND THIRD GRADE STUDENTS: A MULTILEVEL ANALYSIS - Paleczek, Lisa; Seifert, Susanne; Gasteiger-Klicpera, Barbara (Psychology in the Schools)
Keywords: Developmental and Educational Psychology; Education

Mathematics-related Competence of Early Childhood Teachers Visiting a Continuous Professional Development Course: An Intervention Study - Bruns, Julia; Eichen, Lars; Gasteiger, Hedwig (Mathematics Teacher Education and Development (MTED))
Recent studies highlight early childhood teachers’ mathematics-related competence. Developing this competence should be a main aspect of early childhood teachers’ education. This is, however, not the case in all countries. Consequently, high-quality professional development courses are needed. Based on research results, we developed a competence-oriented continuous professional development course ("EmMa") and examined the effects of "EmMa" by asking: How does "EmMa" affect the development of early childhood teachers’ i) mathematical content knowledge, ii) mathematical pedagogical content knowledge and iii) beliefs towards mathematics in general? To answer these questions, we conducted a pre-test/post-test study including a control group with 99 in-service early childhood teachers. Results show that the course affected teachers’ mathematical pedagogical content knowledge and static orientation towards mathematics positively. From this we conclude that scaling-up "EmMa" might be a suitable approach to bridge the gap between pre-service education with nearly no mathematics and the challenges of early mathematics education.
Keywords: Beliefs; Competency Based Teacher Education; Control Groups; Early Childhood Education; Faculty Development; Foreign Countries; Inservice Teacher Education; Intervention; Mathematical Aptitude; Mathematics Skills; Pedagogical Content Knowledge; Preschool Teachers; Pretests Posttests; Professional Continuing Education; Statistical Analysis; Teacher Competency Testing

Interventionsstudie zur Entwicklung mathematikbezogener Einstellungen frühpädagogischer Fachpersonen - Eichen, Lars; Bruns, Julia (Frühe Bildung)
Keywords: competency development; early childhood mathematics education; professional development course

Brauchen mehrsprachige Jugendliche eine andere fach- und sprachintegrierte Förderung als einsprachige? - Prediger, Susanne; Wessel, Lena (Zeitschrift für Erziehungswissenschaft)
Keywords: Education

Is Formal Language Proficiency in the Home Language Required to Profit from a Bilingual Teaching Intervention in Mathematics? A Mixed Methods Study on Fostering Multilingual Students’ Conceptual Understanding - Schüler-Meyer, Alexander; Prediger, Susanne; Kuzu, Taha; Wessel, Lena; Redder, Angelika (International Journal of Science and Mathematics Education)
Keywords: General Mathematics; Education

The crucial first year: a longitudinal study of students’ motivational development at a Swiss Business School - Brahm, Taiga; Jenert, Tobias; Wagner, Dietrich (Higher Education)
In Switzerland, every student graduating from grammar school can begin to study at a university. This leads to high dropout rates. Although students’ motivation is considered a strong predictor of performance, the development of motivation during students’ transition from high school to university has rarely been investigated. Additionally, little is known about the relation of motivational aspects with other influences on study performance. The present longitudinal study addresses this research gap and examines the development of economics and management students’ study motivation. It encompasses four waves of data collected throughout the first year, using quantitative online surveys. In total, the sample consists of 820 students. Data is analysed using latent change modelling. Results indicate that students start at a higher level of intrinsic motivation compared to extrinsic motivation. The variability of the starting value of the two constructs is also differing. The analysis also shows a gradual decline in students’ motivation. Above all, the transition from secondary to higher education seems to be a driver for this decline.
Keywords: Transition to higher education; Motivation; Longitudinal study; Socio-cultural factors; Latent change model; Switzerland

Suggestions for Vocabulary Focused Reading Lessons for Mainstream Classrooms Addressing Both L1 and L2 Learners - Seifert, Susanne; Kulmhofer, Andrea; Paleczek, Lisa; Schwab, Susanne; Gasteiger-Klicpera, Barbara (Early Childhood Education Journal)
Keywords: Developmental and Educational Psychology; Education

The self-fulfilling prophecy of fear of academic failure - Brahm, Taiga; Jenert, Tobias; Wagner, Dietrich
Academic success in Higher Education is influenced by a number of different factors. This paper tackles the question if the individual levels of motivation, anxiety, enjoyment and self-efficacy, measured immediately before entering university, influence the probability of academic success. Former studies have shown an influence of the high school grade, the learning environment and motivational variables. They do not investigate, however, the individual levels of the mentioned constructs before the beginning of the studies. This research was conducted at the University of St. Gallen/Switzerland. The sample includes 695 first-year students who provided information about the individual level of the mentioned constructs. Descriptive statistics show that on average the students are highly motivated, have a high level of self-efficacy and are looking forward to their studies before their beginning. Yet, there are students who have a high level of fear of failure in the study in spite of their high motivation and self-efficacy. A logistic regression shows that there is a significant effect of fear of failure on the probability of study success. This paper shows that fear of failure can increase the probability of academic failure and thus become a self-fulfilling prophecy. It confirms fear as an important factor for academic success. Furthermore, other important factors for academic success, for example the high school grade, could be confirmed in this study
Keywords: Quantitative methods; Student learning; Emotion and Cognition; Social sciences; Higher education; Motivation and Emotion; Fear of Failure

A person-centred approach to students' transition into Higher Education - Brahm, Taiga; Wagner, Dietrich; Jenert, Tobias
A highly selective first study phase in many Swiss study programs leads to a rather competitive climate among students. However, the atmosphere at the university is an important factor for students' transition into Higher Education. An important question in this context is whether students' are equipped with different dispositions influencing how they cope with this transition. Other research has already shown that different groups of students can be identified regarding their student behavior. Yet, so far little is known about patterns of variables characterizing students, transitioning successfully. The paper takes advantage of a person-centered approach, i.e. the latent-class analysis, which makes it possible to identify groups of individuals, sharing common attributes. The research was conducted as a longitudinal study during their first year at a Swiss university. The return rate was about 67%, with 820 utilizable questionnaires at t1. Based on the analysis of students' anxiety, intrinsic motivation and self-efficacy, three distinct classes of students could be identified. The first class can be called the "highly motivated and self-confident" students. The second class is characterized by the same pattern, however, on a more intermediate level and the last class can be described as the "least motivated and most anxious" group of students. This study contributes to research and theory on students' transition into higher education and could be a first hint that students' experiences of this transition can vary substantially.
Keywords: Quantitative methods; Self-efficacy; Higher education; Motivation and Emotion

Zwischen Individuum, Institution und Disziplin: Methodologische Überlegungen zur Erfassung von Lernkulturen an Hochschule - Jenert, Tobias; Reinmann, Gabi (Dokumentation der Jahrestagung der Sektion Erwachsenenbildung der DGfE)
Keywords: Methodologie; Lernforschung; hochschuldidaktische Forschung; Higher Education

Effects of a Whole-Class Reading Program Designed for Different Reading Levels and the Learning Needs of L1 and L2 Children - Seifert, Susanne; Schwab, Susanne; Gasteiger-Klicpera, Barbara (Reading & Writing Quarterly)
Keywords: Linguistics and Language; Education

Massification of Higher Education in Taiwan: Shifting Pressure from Admission to Employment - Chan, Sheng-Ju; Lin, Liang-Wen (Higher Education Policy)
Keywords: Sociology and Political Science; Education

On the assessment of attitudes towards studying—development and validation of a questionnaire - Brahm, Taiga; Jenert, Tobias (Learning and individual differences : journal of psychology and education)
This research aims to develop and validate an instrument for the assessment of attitudes towards two particular objects: the Higher Education Institution (HEI) and the process of studying. Investigating attitudes towards studying at a HEI in a comprehensive way addresses an important research gap. It connects students' perception of the institution with teaching and learning. To validate the Assessment of Students' Attitudes towards Studying (ASAtS) Questionnaire, data was gathered at three different universities in Switzerland (820 students), Sweden (167) and Germany (133). Overall, the results show the internal consistency of the ASAtS. Its nomological validity is also supported by correlations with other constructs, such as intrinsic motivation and study performance. The ASAtS contributes to the theory on students learning by broadening the scope of research beyond learning in a narrow sense. From a practical point of view, it provides a tool for HE management to monitor students' perception of their HEI.
Keywords: Attitude; Student learning; Higher Education Institution; university; student experience

Developing study programs as a continuous task-the role of educational developers - Brahm, Taiga; Zellweger, Franziska; Jenert, Tobias; Thomann, Geri
Abstract Summary: Study programs are currently receiving more attention in Europe. In consequence, it can be observed that the roles of program development and management are professionalized. In the proposed round table, we would like to discuss the role of educational developers to support this professionalization via measures of training and process support in the light of recent developments in Switzerland. Abstract Text: Professionalization of program development as an institutional responsibility In Switzerland, different developments in higher education have led to increased attention to the development and management of the study programs such as the Bologna process, an increasingly competitive environment, the tertiarisation of a number of professions formerly acquired through vocational education. Furthermore, the national qualification framework and in particular accreditation processes require HEI to demonstrate the effectiveness of their activities (e.g., Sursock & Smit, 2010). Many different actors have been involved in development processes on the program level but also within educational development units. However, so far a systematic discourse on key issues regarding the management and development of study programs is missing, not only in German-speaking Europe. The following main question will guide the round table session: How can educational development give vital impulses for program development? Our starting points are two approaches or frameworks from Swiss HEI: a) the definition of competencies for new program professionals at the Zurich University for Teacher Education and b) a process for the strategic development of didactically-aligned study programs at the University of St. Gallen. Framework 1: Competencies for program managers The experiences with a training program for study program managers at the Zurich University for Teacher Education are reported. Over a period of four years, a competency profile has been developed and refined. Insights into the challenges and struggles of this role were gained. Despite diverse job characteristics of program managers (often resulting from an institution-specific history), there is a common set of competencies necessary to successfully cope with organizational complexity such as role competency (Schein, 1992) and lateral leadership (Kühl et al., 2005). Framework 2: Towards a systematic development of study programs The second initiative concerns the strategic approach to program development implemented at the University of St. Gallen (Brahm & Jenert, 2013; Jenert, 2011). In this structured process, the program goes through four process steps: process initiation, program analysis, program development, evaluation of the process and results. A major challenge in this process is the role of program professionals. The goal is to establish them as change agents for a didactically-aligned study program. Outcome: Role of educational development After briefly introducing the two examples, the roles of program professionals and educational development in HEI will be discussed. The questions guiding the discussion will be: • How can program development be established as a continuing task, closely tied to quality development? • How can the competencies of program professionals be developed and the local capacity and ownership be strengthened? • How can educational development support program development and provide vital impulses? Audience Engagement. Depending on the number of participants, first the questions will be discussed in groups. To put the results of the discussion on record, it will be summarized and uploaded in our weblog for further discussion after the session.
Keywords: curriculum development; study programs; Bologna; educational development; higher education

The crucial first year: The development of students' motivation at a Business School-a Mixed Methods Study - Brahm, Taiga; Jenert, Tobias
The transition from school to university can be overwhelming for some students. While students' motivation is considered a strong predictor of performance, the development of motivation during students' transition from high school to university has rarely been investigated. Additionally, little is known about the relation of motivational aspects with other influences on study performance. The present mixed methods study addresses this research gap and examines the development of economics students' study motivation. The longitudinal mixed-method study included three waves of data collected using quantitative surveys and a series of five interviews conducted with 14 first-year students over eight months. Regarding students' development over time, the quantitative analysis showed a gradual decline in students' motivation. However, in the interviews, certain events during the first year were identified as critical incidents demotivating students. These insights into the development of students' motivation at a business school show that concrete incidents influence students' motivational development; thus, they could be transformed by structural changes.
Keywords: motivation; business school; higher education; latent growth curve model; longitudinal study; mixed methods; interview; students

Transition within higher education institutions (HEI): Differences in learning culture (LC) between first-year, bachelor, and master students at a business school - Gebhardt, Anja; Jenert, Tobias
Tertiary education comprises at least two phases, undergraduate and graduate studies. Often, the first year is regarded another, crucial phase where students familiarize with the study environment. It can be hypothesized that students' individual perceptions of learning and studying as well as the pedagogies they experience differ depending on their current study phase. Yet, differences between the phases in HE have rarely been investigated. To capture differences in student experiences in HE comprehensively, Jenert and Gebhardt (2010) have developed a framework describing Learning Culture in HEI. LC comprises a number of constructs on the three levels of the individual student, pedagogical interactions and the organization. The study first aims to quantitatively describe differences in LC between the phases of HE within a university. Based on this analysis, a second goal is to develop a deeper understanding of how students manage the transitions between different phases by applying qualitative research methods.
Keywords: Higher Education; Transitions; Bachelor; Master

Improving reading in children with German as a first or second language - Schwab, Susanne; Seifert, Susanne; Gasteiger-Klicpera, Barbara (International Journal of Early Years Education)
Keywords: Developmental and Educational Psychology; Education

Encouraging Family and Parent Education: Program Development and Evaluation in the Federal State of Baden-Württemberg, Germany - Landhäußer, Sandra; Faas, Stefan; Treptow, Rainer (Center for Educational Policy Studies Journal (CEPS))
Against the background of a European-wide strategy of governance aimed at improving support for parents and families, the following report details the conceptualization and evaluation of a federal state program4 in Baden- Württemberg (Germany) which was launched in 2008 to encourage fam- ily and parent education. Two program components, a voucher system for parents with a new-born child and an element that emphasizes educa- tional offers for families with special needs in particular living situations, were started to increase requests for educational courses. The aim was to establish and deepen cooperation between different public and private professional services that are in contact with parents and their children. The results show that main goals of the program were reached.
Keywords: family and parent education; cooperation; voucher system; support for families with special needs in particular living situations; program evaluation

Prospective physics teachers' pedagogical content knowledge. Validating a test instrument by using a think aloud study - Gramzow, Yvonne; Riese, Josef; Reinhold, Peter (E-Book Proceedings of the ESERA 2013 Conference: Science Education Research For Evidence-based Teaching and Coherence in Learning. Part 13)
In research, pedagogical content knowledge (PCK) is considered as an important aspect of teachers’ professional competence. However, there is no standardized definition concerning the internal structure of this concept, especially in science subjects such as physics. Therefore, results of different empirical studies measuring PCK are difficult to compare. Moreover, there is no study that can report on correlations between various aspects of PCK. Against this background, different conceptualizations and theoretical considerations of PCK have been consulted and compared. Based on these analyses, a comprehensive model of prospective physics teachers’ PCK and a related test instrument (in the form of a pen-and-paper test) have been developed. Its purpose is to enlighten the correlations between certain aspects of PCK as well as between PCK and other areas of knowledge (e.g. content knowledge). To validate the test instrument and the underlying PCK model, a think aloud study with 15 probands was conducted. We focused on the knowledge areas that the probands referred to while answering the items. With these data, indications of the validity of the underlying model could be identified. Furthermore, the test instrument was piloted with a sample of 216 prospective physics teachers.
Keywords: PCK; teacher education; physics; think aloud study

On the assessment of attitudes towards the study process and the university: Attitudes towards the Study Environment Questionnaire (ASEQ) - Brahm, Taiga; Jenert, Tobias; Euler, Dieter
The purpose of the research was to develop and validate an instrument for the assessment of attitudes towards the study environment in higher education contexts. The questionnaire is designed to measure students' attitudes towards two particular objects: the university (or Higher Education Institution) and the process of studying. Five studies at two different universities were conducted to develop and validate the Attitudes towards the Study Environment Questionnaire (ASEQ). In total, 1640 students filled in the questionnaire. Reliability tests and exploratory factor analysis as well as confirmatory factor analysis showed satisfactory psychometric characteristics of the ASEQ. Each part of the questionnaire is internally consistent and construct validity of the scales is supported by correlations with other constructs as assumed by current theories: Positive attitudinal constructs (normative behavior, autonomy, joy, self-efficacy, and task value) are positively related to intrinsic motivation and the expected study performance while anxiety is negatively related to these constructs. Since attitudes towards the study situation are connected to student engagement and motivation, the study contributes to the theory of student learning by providing a validated instrument to assess attitudes. Thus, the ASEQ can support further research on student performance and development by providing an instrument for the hitherto neglected but nonetheless extremely relevant domain of attitudes. Also, the questionnaire can be used as a diagnostic instrument for higher education faculty and administration to trace students' attitudinal development over time - a factor of prime importance for student socialization during the introductory phase of studying.
Keywords: attitudes; teaching and learning; studying; higher education institution; theory of planned behavior; instrument development

A latent growth curve analysis of Business students' intrinsic and extrinsic motivation - Brahm, Taiga; Jenert, Tobias
The proposed paper aims to investigate the longitudinal development of students' motivation over the first year of their studies at a business school by using latent growth curve modeling. The study tackles the following core research questions: How do first-year university students' intrinsic and extrinsic vary over time? Which (motivational) factors are related to students' motivational development? Although motivational dispositions have been analyzed extensively in previous studies, their longitudinal development has hitherto not been examined in the higher education context. This longitudinal study is conducted at the University of St. Gallen in Switzerland. The current sample includes 280 first-year students who have been surveyed three times and who are representative of the first-year student population. Descriptive results show that prior to their studies, students were motivated most by intrinsic factors, however, extrinsic motivation was also quite high. Employing latent growth curve modeling, it could be shown that both intrinsic and extrinsic motivation decline significantly over the course of the first year (8 months). The study contributes to motivation theory by providing further insights into the development of academic motivation over time. Latent growth curve modeling as a method can be well used for longitudinal data analysis, thus, excluding measurement error from longitudinal data. Furthermore, the study supports educational developers by determining factors influencing students' motivational development.
Keywords: motivation; intrinsic motivation; extrinsic motivation; latent growth curve modeling; longitudinal data analysis; ASEQ; higher education; studying

Learning by Doing – Improving Academic Skills - Temmen, Katrin; Walther, Thomas (International Journal of Engineering Pedagogy (iJEP))
Engineering faculties generally involve their students in the creation of numerous scientific works and publications. However, students are rarely trained in this area and could well benefit from targeted support: to this end, we propose a specific lecture that addresses the subtleties of scientific research and writing and allows the students to apply and mentally anchor their acquired knowledge while composing a basic scientific term paper.
Keywords: General Engineering; Education

Why Students Procrastinate: A Qualitative Approach - Klingsieck, Katrin B.; Grund, Axel; Schmid, Sebastian; Fries, Stefan (Journal of College Student Development)
Keywords: Education

Fostering German-language learners’ constructions of meanings for fractions—design and effects of a language- and mathematics-integrated intervention - Prediger, Susanne; Wessel, Lena (Mathematics Education Research Journal)
Keywords: Education; General Mathematics

Studienprogramme als didaktische Gestaltungs-und Untersuchungseinheit: Theoretische Grundlegung und empirische Analyse - Jenert, Tobias
Mit welchen Erwartungen und Anforderungen sehen sich Studierende im Hochschulalltag konfrontiert? Wie muss nach Ansicht der Studierenden gehandelt werden, um das Studium "erfolgreich" zu bewältigen? Wie laufen die Auswahl unterschiedlicher Lernaktivitäten im Studium sowie die Allokation von Ressourcen im Detail ab? Diese und weitere Fragen sind vor allem im Zusammenhang mit der Debatte um die Bologna-Reform stärker in den Mittelpunkt gerückt. Denn während modularisierte Curricula und Credit-Point-Systeme oft nach administrativ-organisatorischen Gesichtspunkten eingeführt wurden, hat die Gestaltung der Studienstrukturen auf Programmebene zwangsweise Auswirkungen auf das Studienhandeln - und damit auch auf das Lernen der Studierenden. Es gibt viele Vermutungen über die "Wirkungen" von Bologna auf das Studieren: Die Rede ist von Verschulung, Entwissenschaftlichung und Arbeitsüberlastung und Studierende stehen im Verdacht, ihren Studienpfad eher im Sinne einer Credit-Point-Jagd denn interessengeleitet zu gestalten. In der Regel bleibt es dabei jedoch bei anekdotischen Beobachtungen - es fehlt bislang an gesicherten Erkenntnissen über Zusammenhänge zwischen Bologna-konformen Studienkontexten und dem Handeln Studierender. Denn obschon Studierende seit langem Gegenstand der Forschung sind, ist bislang wenig darüber bekannt, wie sie den langfristigen Bildungsprozess eines ganzen Studiums gestalten. Stattdessen wurde vorwiegend das Lernen im engeren Sinne, das so genannte "Classroom Learning" untersucht. Diejenigen, die Studienprogramme nach didaktischen Gesichtspunkten gestalten wollen müssen wissen, wie Studierende mit unterschiedlichen Studienstrukturen umgehen. Denn nur so ist eine planvolle Programmgestaltung im Sinne pädagogischer Zielsetzungen und didaktischer Prinzipien möglich. Die vorliegende Arbeit nimmt diese Problemstellung auf und untersucht, welche Zielvorstellungen und Handlungsstrategien Studierende bei der Bewältigung ihres Studienalltags in unterschiedlichen Bologna-konformen Studienprogrammen entwickeln. Im Einzelnen wird gefragt, (1) welche Vorstellungen, Wahrnehmungen und Handlungslogiken das Handeln Studierender in unterschiedlichen Studienprogrammen prägen und (2) welche programmspezifischen Kontextbedingungen die Herausbildung dieser handlungsleitenden Charakteristika beeinflussen. Ausgehend von diesen beiden Fragestellungen wird zunächst ein theoretisch fundierter Analyserahmen für Studienprogramme entwickelt. Darauf aufbauend werden verschiedene Studienprogramme empirisch untersucht, um schliesslich Design-Prinzipien für die Gestaltung von Studienprogrammen zu formulieren. Es wird nicht davon ausgegangen, dass Studienstrukturen das Handeln Studierender im Sinne eines kausalen Wirkungszusammenhangs bestimmen. Vielmehr wird gefragt, was die Studierenden mit den Strukturen, auf die sie treffen, machen. Studienprogramme werden als kulturelle Einheiten verstanden, innerhalb derer sich spezifische handlungsleitende Vorstellungen und Normen entwickeln. Diese impliziten Regeln des Studienhandelns - das so genannte "Hidden Curriculum" - und vor allem auch die dahinterliegenden Konstruktionsprozesse aufzudecken, ist Ziel dieser Arbeit.
Keywords: Studierverhalten; Hochschuldidaktik; Lernpsychologie; Kulturpsychologie; Bologna-Prozess; Curriculumentwicklung; Hochschulbildung; Study programme; Bologna-process; educational development; cultural psychology; higher education; curriculum development

Studienprogramme als hochschuldidaktische Gestaltungs-und Untersuchungseinheit - Jenert, Tobias
In den vergangenen Jahren wurden viele Vermutungen über die "Wirkungen" von Bologna auf das Studieren geäussert: Schlagworte wie Verschulung oder Entwissenschaftlichung sind zu hören und Studierende stehen im Verdacht, ihr Studium eher als Credit-Point-Jagd denn interessengeleitet zu gestalten (z.B. Stegemann, 2007, o. S.; Schultheis, et al. 2008). Meist handelt es sich jedoch um anekdotischen Beschreibungen, bis auf wenige Ausnahmen fehlen empirisch belegte Erkenntnisse.1 Denn obschon Studierende seit langem Gegenstand der Forschung sind, ist bislang wenig darüber bekannt, wie sie den langfristigen Bildungsprozess eines ganzen Studiums gestalten. Vorwiegend wurde Lernen im engeren Sinne, das so genannte "Classroom Learning" untersucht (Aineley, 2008). Forschungsfokus. Die diesem Beitrag zugrunde liegende Studie nimmt diese Forschungslücke auf und untersucht Zielvorstellungen und Handlungsstrategien Studierender bei der Bewältigung ihres Studienalltags in unterschiedlichen Bologna-konformen Studienprogrammen. Im Einzelnen wird gefragt, (1) welche Vorstellungen und Wahrnehmungen das Handeln Studierender prägen und (2) welche programmspezifischen Kontextbedingungen die Herausbildung dieser handlungsleitenden Charakteristika beeinflussen. Als theoretischer Rahmen wurde die so genannte Kulturpsychologie herangezogen, die Handeln als Resultat einer Wechselwirkung von individuell-psychischen Merk-malen und sozio-kulturell vermittelten Vorstellungen versteht (Shweder, 1991; Bruner, 1990).
Keywords: Hochschulentwicklung; Studienprogramme; Curriculum Development; Higher Education; Faculty Development

" Nur" didaktisch oder auch strategisch?: Strukturelle Verankerung, Aufgaben-und Wirksamkeitswahrnehmungen hochschuldidaktischer Einrichtungen in Deutschland - Jenert, Tobias; Brahm, Taiga
Die Lehrpraxis an Hochschulen breitenwirksam und nachhaltig zu verbessern, gehört zu den schwierigsten Herausforderungen für die Hochschuldidaktik. Ein möglicher Weg besteht darin, als hochschuldidaktische Einrichtung stets mit Blick auf die Gesamtstrategie der Hochschule und Anspruchsgruppen in der Hochschulleitung und -administration zu agieren (Jenert & Brahm, 2010). Es stellt sich die Frage, welche Vorstellungen bezüglich der eigenen Aufgaben und der Wirksamkeit des eigenen Handels hochschuldidaktische Stellen in Deutschland haben. Mit einer Online-Befragung von Leitungspersonen im Bereich Hochschuldidaktik und -entwicklung in Deutschland konnten 35 Personen (72 angeschrieben) erreicht werden, wobei sich ein breiter Querschnitt verschiedener Einrichtungen ergab. Abgefragt wurden (1) Struktur und institutionelle Anbindung der Einrichtung, (2) Wahrnehmung der eigenen Wirksamkeit sowie (3) Aufgabenschwerpunkte und notwendige Kompetenzen. Die Ergebnisse zeigen, dass einerseits ein Bewusstsein für Herausforderungen jenseits didaktischer Aus- und Weiterbildung besteht und die strategische Dimension erkannt ist. Gleichzeitig zeigt die Betonung "traditioneller" Aufgaben und Kompetenzen, dass die strategische Dimension im Tagesgeschäft oft noch keine zentrale Rolle spielt.
Keywords: Hochschulentwicklung; higher education development; Hochschuldidaktik

Die professionelle Kompetenz angehender Physiklehrkräfte in verschiedenen Ausbildungsformen - Riese, Josef; Reinhold, Peter (Zeitschrift für Erziehungswissenschaft)
Keywords: Education

Weblogs zur Unterstützung der Theorie-Praxis-Integration in der Wirtschaftslehrenden-Ausbildung - Jenert, Tobias; Gebhardt, Anja; Käser, Reto (Zeitschrift für E-Learning)
Eine zentrale Herausforderung in der Ausbildung angehender Wirtschaftslehrpersonen stellt die sinnvolle Verknüpfung von Theorie- und Praxiserfahrungen dar. Im Rahmen der Ausbildung angehender Wirtschaftslehrpersonen an der Universität St. Gallen wird eine Lernumgebung gestaltet, die eine Verschränkung von Theorie- und Praxiserfahrungen ermöglichen soll. Die Lernprozesse der Studierenden werden dabei durch didaktisch angeleitete Weblogarbeit unterstützt. Trotz der Lernchancen, die sich aus einer Verknüpfung von theoretischen und praktischen Lernphasen ergeben, schätzen die Studierenden den Nutzen der Weblogarbeit als äusserst gering ein. Die Studierenden bei der reflexiven Integration praxisnaher und theoretischer Lernerfahrungen zu unterstützen, ist eine Herausforderung, die dezidierter Anleitung und Förderung durch die Lehrpersonen bedarf
Keywords: Weblog; Blog; e-learning; TEL; higher education; business education

Learning culture as a prerequisite for an institution-wide approach to educational development - Brahm, Taiga; Gebhardt, Anja; Jenert, Tobias
Over the last two decades, the discussion about innovating teaching and learning at higher education institutions (HEI) has concentrated on various core concepts: such as an increased focus on learning outcomes as competencies and more student-centered teaching. These concepts form part of what Barr and Tagg (1995) have termed the "shift from teaching to learning". However, very few approaches have been proposed so far in the scholarly literature on how to actually transfer such normative concepts into the practice of teaching and learning at HEI. In order to sustainably develop the practices of teaching and learning at HEI, it is necessary to comprehend the prerequisites for educational development. The construct of "learning culture" can be seen as a possible concept to explicate these prerequisites. The aims of this study are to (a) propose an institution-wide approach to educational development at HEI and to (b) present a comprehensive instrument to diagnose learning culture as a starting point for educational development. The findings of the study include a first version of the Learning Culture Inventory for HEI. The students' version of the instrument encompasses 12 scales for the individual, 12 for the pedagogical interactions and 5 for the organizational dimension. The assumed basic factor structure of the instruments could be confirmed. With the institution-wide approach to educational development and the Learning Culture Inventory, this study can provide the basis for sustainable developmental initiatives to innovate teaching and learning at HEI.
Keywords: higher education; instrument development; strategy; educational development

,,Blended Professionals´´ als Akteure einer institutionsweiten Hochschulentwicklung - Jenert, Tobias; Brahm, Taiga (Zeitschrift für Hochschulentwicklung)
Die aktuelle hochschuldidaktische Diskussion ist durch Schlüsselbegriffe wie Outcome- und Kompetenzorientierung geprägt. Allerdings sind die Strategien zur nachhaltigen Gestaltung der Lehr- und Lernpraxis bisher nur wenig differenziert. Der Beitrag stellt das Konzept einer "institutionsweiten Hochschulentwicklung" vor. Dieses spricht individuelles Handeln von Lehrenden und Lernenden sowie curriculare und organisationale Aspekte an. Mittels Experteninterviews wird gezeigt, dass Hochschulentwicklung eine "Third-Space-Funktion" zwischen Akademie und Administration einnimmt. Das personelle Profil solcher Einrichtungen verlangt nach "Blended Professionals", die sowohl als Servicepersonal als auch als Mitglieder der akademischen Welt wirkungsvoll agieren können.
Keywords: Hochschulentwicklung; educational development; higher education; Hochschuldidaktik

Learning Cultures at Higher Education Institutions: Outlining a wohle-institution approach to teaching and learning - Jenert, Tobias; Gebhardt, Anja
Keywords: earning culture; Lernkultur; whole-institution approach; higher education; Hochschule

Lernkulturen an Hochschulen: Theoretische Überlegungen zur Betrachtung studentischen Lernens unter individueller, pädagogischer und organisationaler Perspektive - Jenert, Tobias; Zellweger, Franziska; Dommen, Jenny; Gebhardt, Anja
Keywords: Lernkultur; Hochschule; HEI; learning culture; higher education; teaching and learning; Hochschullehre